Mysterious sphingolipids: metabolic interrelationships at the center of pathophysiology - Jamjoum, Rama; Majumder, Saurav; Issleny, Batoul; Stiban, Johnny (Frontiers in Physiology, 2024)
Metabolic pathways are complex and intertwined. Deficiencies in one or more enzymes in a given pathway are directly linked with genetic diseases, most of them having devastating manifestations. The metabolic pathways undertaken by sphingolipids are diverse and elaborate with ceramide species serving as the hubs of sphingolipid intermediary metabolism and function. Sphingolipids are bioactive lipids that serve a multitude of cellular functions. Being pleiotropic in function, deficiency or overproduction of certain sphingolipids is associated with many genetic and chronic diseases. In this up-to-date review article, we strive to gather recent scientific evidence about sphingolipid metabolism, its enzymes, and regulation. We shed light on the importance of sphingolipid metabolism in a variety of genetic diseases and in nervous and immune system ailments. This is a comprehensive review of the state of the field of sphingolipid biochemistry.